Keanekaragaman Tanaman Buah di Kebun Raya Indrokilo dalam Upaya Konservasi Tanaman Lokal Kabupaten Boyolali - Ismilda Fauziah; Talitha Naswa Allysa (Jurnal Informasi, Sains dan Teknologi, 2024)
Kebun Raya Indrokilo, Boyolali (KRIB) is one of the biodiversity preservation places that serves as a location for conservation, research, education, recreation, and protection for various plants that are threatened with extinction due to habitat quality degradation. One of the collections from KRIB that has an important function for the environment is local fruit plants that are increasingly rare. So the purpose of this research is to identify local fruit plants preserved at KRIB and determine their conservation status on the IUCN Red List. This research method is descriptive qualitative and literature study by checking the conservation status and observation of local plant species and their number from the object of research. The results show that there are 58 local fruit plant species from 22 different families that have conservation status in the IUCN Red List. The existing conservation status is LC (Least Concern), EN (Endangered), EW (Extinct in the Wild), and DD (Data Deficient). A total of 26 species have LC status, 1 species has EN status, 1 species has EW status, and 30 other species have DD status. It can be concluded that 58 species of local fruit plants in Indrokilo Botanical Garden, Boyolali have a conservation status on the IUCN Red List.